ONLINE VOCABULARY GAMES: POTENTIAL ENCHANCEMENTS OF STUDENTS' VOCABULARY ACQUISITION: A qualitative study of 4th Grade of Primary students in one of the International Schools, Bandung - Samudro, Eko G (2015)
Penelitian yang berjudul "Online Vocabulary Games: Potential Enhancements of Students' Vocabulary Acquisition" ditujukan pada isu akan pentingnya permainan kosakata online dalam pembelajaran kosakata. Penilitian ini bertujuan dalam mengungkap cara-cara permainan kosakata online sebagai media yang berpotensi meningkatkan kemampuan kosakata siswa dalam membantu siswa mempelajari kosakata Bahasa Inggris. Beberapa permainan kosakata online dari www.eslgamesplus.com dan www.vocabulary.co.il dipilih untuk melakukan penelitian. Unsur-unsur yang ada pada permainan kosakata online, seperti, ilustrasi gambar, interaksi antar pemain, kompetisi, animasi temasuk bunyi dan suara, umpan balik langsung, konteks, dan penyelesaian masalah dipercaya dapat membantu proses pembelajaran siswa. Terdapat sepuluh siswa kelas 4 yang menjadi subyek penelitian. Penelitian ini menggunakan metode kualitatif. Kerangka penelitian oleh Wood (2001) dan Yip dan Kwan (2006) digunakan dalam membantu penelitian ini. Setelah dilakukan pembelajaran kosakata dengan permaianan kosakata online, siswa diberikan permainan hangman yang berkaitan dengan kosakata yang terdapat di permainan kosakata online di akhir pertemuan. Pemenang dari permainan adalah tim siswa perempuan yang mencakup siswa berkemampuan tinggi dan menengah. Berdasarkan hasil dari kuesioner, permainan kosakata online berperan penting dalam membantu pembelajaran kosakata Bahasa Inggris siswa melalui unsur-unsur yang disebutkan sebelumnya. Hasil dari wawancara juga menunjukkan bahwa unsur-unsur tersebut, seperti animasi, membantu menciptakan situasi yang nyaman untuk belajar. Selain itu, kompetisi diantara pemain juga memacu siswa untuk mempelajarai kosakata agar bias memenangkan permainan. Hasil kuesioner juga menunjukkan presepsi positif siswa tentang penggunaan permaianan kosakata online ini. Oleh karena ini, penelitian ini dianggap bermanfaat dalam melakukan pembelajaran kosakata Bahasa Inggris dengan cara yang bervariasi. ---------- The paper entitled "Online Vocabulary Games: Potential Enhancements of Students' Vocabulary Acquisition" addresses the issue of the importance of online vocabulary games in learning vocabulary. The research was aimed at discovering the way online vocabulary games as potential enhancements of students' vocabulary acquisition in helping students to learn and retain vocabulary. Some online vocabulary games from www.eslgamesplus.com and www.vocabulary.co.il were selected in order to conduct the research. The elements following the online vocabulary games, which are, pictorial illustration, interaction among players, competition, animation included sounds and music, immediate feedback, context, and problem solving are believed to be helpful in students' learning processes. There were ten students of grade four observed as the subjects of the research. Furthermore, in order to collect and identify the data, the research employs qualitative method. In addition to data analysis, Wood (2001) and Yip and Kwan (2006) frameworks are used for maintaining the way online vocabulary games help students in vocabulary acquisition. The learning processes were observed by conducting field notes. After conducting the vocabulary learning through online vocabulary games in eight meetings, the students were given a "hangman" game related to the vocabularies learned through online vocabulary games. The winner of the games was the girls' team which included the higher and middle achiever in the team. Based on the discussion of the questionnaire analysis, the findings showed that the online vocabulary games play important role in helping students' vocabulary learning processes through the elements mentioned before. The result of interview also provides the students' confirmation towards the helpful elements of online vocabulary games such as, the animation, sounds and music helped them to create relaxing atmosphere to learn vocabulary happily. The competition among them also helped the students to win the game by mastering vocabularies well. The questionnaires also mentioned the positive result of students' perceptions towards online vocabulary games in the classroom session. Thus, it can be concluded that the students' responses towards the online vocabulary games were positive. The research is beneficial for teachers to conduct various ways in teaching vocabularies.